2013
DOI: 10.1103/physrevb.88.245415
|View full text |Cite
|
Sign up to set email alerts
|

Shot noise in lithographically patterned graphene nanoribbons

Abstract: We have investigated shot noise and conductance of multi-terminal graphene nanoribbon devices at temperatures down to 50 mK. Away from the charge neutrality point, we find a Fano factor F ≈ 0.4, nearly independent of the charge density. Our shot noise results are consistent with theoretical models for disordered graphene ribbons with a dimensionless scattering strength K0 ≈ 10 corresponding to rather strong disorder. Close to charge neutrality, an increase in F up to ∼ 0.7 is found, which indicates the presenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
4
13
0
Order By: Relevance
“…It is found that the Fano factors at 0 T are ∼0.5 far from the charge neutral point and they are enhanced around the charge neutral point. Among several experimental works on this topic 21 22 23 , our result agrees with that for graphene nanoribbon 23 , which reported F ∼0.4. According to theoretical studies 24 25 , the Fano factors at 0 T strongly depend on the disorder strength, which could explain the present results.…”
Section: Resultssupporting
confidence: 89%
“…It is found that the Fano factors at 0 T are ∼0.5 far from the charge neutral point and they are enhanced around the charge neutral point. Among several experimental works on this topic 21 22 23 , our result agrees with that for graphene nanoribbon 23 , which reported F ∼0.4. According to theoretical studies 24 25 , the Fano factors at 0 T strongly depend on the disorder strength, which could explain the present results.…”
Section: Resultssupporting
confidence: 89%
“…The measured conductivities correspond to a field effect mobility of cm 2 /Vs, which is by a factor of two smaller than in the graphene cross experiments of ref. 25 . Some asymmetry in conductances is observed at and V. However, the asymmetry in these regions is bias dependent and its influence on cross correlations becomes reduced by using a fixed current-level correlation determination if necessary (For a linear cross-shaped conductor, when switching to measurement configuration C, the currents at terminals 1 and 3 double from the single source configurations A and B.…”
Section: Resultsmentioning
confidence: 99%
“…46,62,96,158,160,162,[164][165][166]174,176,186,195,196,[199][200][201][202][203][204][205][206]230,and 238) with exception of the previously highlighted experiments and Refs. 157,187, and 211 that did not provide sufficiently high resolution data to make a clear statement.…”
Section: B Observation Of Coulomb Blockadementioning
confidence: 90%
“…From all references presenting data at low temperature over a large range of charge carrier densities (see Refs. 46,56,61,62,96,[156][157][158][159][160]162,[164][165][166]168,173,174,176,180,[186][187][188][189]191,[194][195][196][197][198][199][200][201][202][203][204][205][206]210,211,213,[217][218][219]227,229,233,and 237), most agree that for sufficiently narrow ribbons at sufficiently low temperatures, transport is strongly suppressed. Typically, the conductance decreases with increasing gate voltage until at a certain point conductance is nearly completely suppressed.…”
Section: A Suppressed Conductancementioning
confidence: 99%